EKSPLORASI KEMAMPUAN BERPIKIR KRITIS MELALUI PROJECT MIND MAPPING BERBASIS CANVA PADA PEMBELAJARAN SEJARAH SISWA KELAS XI SMK BASTREN NURUSSALAM - Maghfiroh, Nurholisah Rahayu; Badri, Mohamad Il; Hamdani, M. Iqbal Ibrahim (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study addresses the problem of low critical thinking skills and passive student involvement in history learning, which is still dominated by teacher-centered instruction. The purpose of this study is to describe the implementation of Project Based Learning (PjBL) integrated with Canva-based mind mapping techniques, explore students' critical thinking skills based on Facione's six indicators, and identify supporting and inhibiting factors during implementation. This research utilized a qualitative approach with a descriptive qualitative design. Data were collected through observation, semi-structured interviews, and documentation involving a history teacher and eleventh-grade students at SMK Bastren Nurussalam selected via purposive sampling. Data analysis was conducted using the Miles, Huberman, and Saldana model (data reduction, data display, and conclusion drawing/verification), with source and technique triangulation for data validity. The results indicated that the PjBL model with Canva-based mind mapping was executed systematically through all syntax stages, fostering an active and student-centered learning environment. The implementation facilitated the emergence of all six critical thinking indicators (interpretation, analysis, evaluation, inference, explanation, and self-regulation) during group discussions, digital project creation, and presentations. Supporting factors, such as teacher readiness, technological infrastructure, and student enthusiasm, predominated over minor obstacles like internet instability and varying digital skills, which were effectively mitigated by teacher guidance. In conclusion, the PjBL model combined with Canva-based mind mapping is an effective strategy to enhance student engagement and critical thinking skills in history education.